METHODOLOGY OF STEP-BY-STEP ORGANIZATION OF STILL LIFE DRAWING LESSONS - Rahimova Gulhayo Qahramonovna, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: The article discusses the methodology of step-by-step organization of still life drawing lessons in general education schools. It focuses on the development of students’ visual perception, aesthetic taste, and artistic thinking through systematic teaching methods. The author emphasizes that consistent stages of still life drawing — such as observation, composition, color harmony, and creative interpretation — help students better understand artistic structure and express national and individual values through art. The study also highlights the importance of using innovative teaching technologies, visual aids, and interdisciplinary connections to enhance the effectiveness of the educational process. The gradual organization of lessons improves students’ creative activity, artistic competence, and motivation toward fine arts.